Wow!!thats a word from the old english that made it
F(g(-2))=4(-2)^6+4(-2)^3+1
f(g(-2))=4(64)+4(-8)+1
f(g(-2))=256-32+1
f(g(-2))=224+1
f(g(-2))=225
Answer:=
Solution: -2<c<3
Interval Notation: (-2,3)
Step-by-step explanation:
-3<5c+7<22
-3<5c+7 : c>-2
5c+7<22 : c<3
combine the intervals
c>-2 and c<3
-2<c<3
Answer:
A) m < -175/k and B) 3c/5 - 11
Step-by-step explanation:
A) Add 90 to both sides. -mk > 175.
Next, divide both sides by -k. Because you divide by a negative, don't forget to reverse the sign!
m < -175/k.
B) Subtract 3c from both sides.
-5f = 55 - 3c.
Now multiply both sides by -1/5.
f = 3c/5 - 11